The evolution of paralogous enzymes MAT and MATX within the Euglenida and beyond - Szabová, Jana; Yubuki, Naoji; Leander, Brian S; Triemer, Richard E; Hampl, Vladimír (BMC evolutionary biology, 2014)
BACKGROUND: Methionine adenosyltransferase (MAT) is a ubiquitous essential enzyme that, in eukaryotes, occurs in two relatively divergent paralogues: MAT and MATX. MATX has a punctate distribution across the tree of eukaryotes and, except for a few cases, is mutually exclusive with MAT. This phylogenetic pattern could have arisen by either differential loss of old paralogues or the spread of one of these paralogues by horizontal gene transfer. Our aim was to map the distribution of MAT/MATX genes within the Euglenida in order to more comprehensively characterize the evolutionary history of MATX. RESULTS: We generated 26 new sequences from 23 different lineages of euglenids and one prasinophyte alga Pyramimonas parkeae. MATX was present only in photoautotrophic euglenids. The mixotroph Rapaza viridis and the prasinophyte alga Pyramimonas parkeae, which harbors chloroplasts that are most closely related to the chloroplasts in photoautotrophic euglenids, both possessed only the MAT paralogue. We found both the MAT and MATX paralogues in two photoautotrophic species (Phacus orbicularis and Monomorphina pyrum). The significant conflict between eukaryotic phylogenies inferred from MATX and SSU rDNA data represents strong evidence that MATX paralogues have undergone horizontal gene transfer across the tree of eukaryotes. CONCLUSIONS: Our results suggest that MATX entered the euglenid lineage in a single horizontal gene transfer event that took place after the secondary endosymbiotic origin of the euglenid chloroplast. The origin of the MATX paralogue is unclear, and it cannot be excluded that it arose by a gene duplication event before the most recent common ancestor of eukaryotes.
Keywords: Gene Transfer, Horizontal; Evolution, Molecular; Methionine Adenosyltransferase; Protozoan Proteins; Phylogeny; Symbiosis; methioninadenosyltransferasa; chloroplasty; protozoální proteiny; Euglenida; molekulární evoluce; Chlorophyta; fylogeneze; Molecular Sequence Data; Chloroplasts; symbióza; molekulární sekvence - údaje; přenos genů horizontální